Understanding Tourists’ Preference for Mammal Species in Private Protected Areas: Is There a Case for Extralimital Species for Ecotourism? - Maciejewski, Kristine; Kerley, Graham I. H. (PloS one, 2014)
Private Protected Areas (PPAs) often use wildlife-based ecotourism as their primary means of generating business. Achieving tourist satisfaction has become a strong driving goal in the management of many PPAs, often at the expense of biodiversity. Many extralimitral species, those which historically did not occur in an area, are stocked in PPAs with the intention of increasing ecotourism attractions. Even though the ecological and economic costs of stocking these species are high, the social benefits are not understood and little information exists globally on the ecotourism role of extralimital species. This study assessed the value of stocking extralimital species using questionnaire-based surveys and observing tourists in Shamwari Private Game Reserve in the Eastern Cape Province of South Africa. No difference was found between indigenous and extralimital species with regards to the tourists' weighted scoring system, average amount tourists were willing to pay, total viewing time, average viewing time or the likelihood of stopping to view species when encountered on game drives. During game drives a strong preference was found for the elephant (Loxodonta africana), lion (Panthera leo), leopard (Panthera pardus) and cheetah (Acynonix jubatus). With the exception of the cheetah, these species are all members of the "big five" and are indigenous. Species availability and visibility, however, may influence the amount of time tourists spend at an animal sighting. Our analysis suggests that certain extralimital species (typically larger and charismatic species) contribute to tourist satisfaction, while particularly the smaller extralimital species add little to the game viewing experience, but add to the costs and risks of the PPAs. We recommend that extralimital species introductions for ecotourism purposes should be approached with caution with regards to the risks to the sustainability of PPAs.